2009
DOI: 10.1007/s12012-009-9058-y
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Cardiac Remodeling in Congestive Heart Failure by β-Adrenoceptor Blockade is Associated with Depression in Sympathetic Activity

Abstract: This study investigated whether improvement in cardiac function and attenuation of cardiac remodeling by some beta-adrenoceptor (beta-AR) antagonists were associated with a depression in sympathetic activity in congestive heart failure (CHF) due to myocardial infarction (MI). Although cardiac dysfunction, hypertrophy and dilatation as well as increased plasma level of catecholamines are known to occur in CHF, the relationship between these parameters is poorly understood. Three weeks after occlusion of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…Since the sympathetic nervous system is markedly activated in heart failure [26,27], the elevated levels of plasma catecholamines are known to play a critical role in the pathogenesis of cardiac dysfunction, cardiac remodelingmediated through the participation of both α-AR and β-AR in the myocardium. Although β-AR blockers have been demonstrated to attenuate myocardial changes in heart failure [27,28], no information regarding the beneficial effects of α-AR blockade on cardiac remodeling or subcellular defects in failing hearts is available in the literature. This study was therefore undertaken to investigate if the depressed cardiac function in rats with heart failure due to MI is improved and cardiac remodeling is attenuated upon treatment with prazosin, a well-known α-AR blocker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sympathetic nervous system is markedly activated in heart failure [26,27], the elevated levels of plasma catecholamines are known to play a critical role in the pathogenesis of cardiac dysfunction, cardiac remodelingmediated through the participation of both α-AR and β-AR in the myocardium. Although β-AR blockers have been demonstrated to attenuate myocardial changes in heart failure [27,28], no information regarding the beneficial effects of α-AR blockade on cardiac remodeling or subcellular defects in failing hearts is available in the literature. This study was therefore undertaken to investigate if the depressed cardiac function in rats with heart failure due to MI is improved and cardiac remodeling is attenuated upon treatment with prazosin, a well-known α-AR blocker.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to test if the beneficial effects of α-AR blockade on subcellular activities occur at the level of cardiac gene expression [23][24][25], changes in mRNA levels for both SR and MF proteins were measured in untreated and prazosin treated hearts. Because of the involvement of sympathetic nervous system activation and subsequent elevated levels of plasma catecholamines in heart failure [26,27], the status of plasma NE, Epinephrine (EPI) and dopamine in MI-induced heart failure was monitored upon treatment with prazosin.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous activation of β-ARs plays an important role in cardiac dysfunction. [6][7][8] Cardiac function was altered in β 1 -AR transgenic mice with cardiac hypertrophy, which could be inhibited by β-AR blockers. 8) Consecutive administration with isoproterenol (ISO), a β-AR agonist, caused cardiac fibrosis in rats.…”
mentioning
confidence: 99%
“…It should be emphasized that there are varying degrees of depression in SL, SR and MF gene expression, protein content and functional activities in hearts subjected to ischemia-reperfusion and these alterations have been attributed to the occurrence of intracellular Ca 2+ overload (7)(8)(9)(31)(32)(33)(34)(35)(36)38). Furthermore, intracellular Ca 2+ overload has been suggested to play a critical role in the development of alterations in SL, SR and MF gene expression, protein content and functional activities in hearts failing due to myocardial infarction (1)(2)(3)(4)(5)(6). Although the exact mechanisms by which intracellular Ca 2+ overload induces changes in cardiac gene expression and subsequent subcellular remodelling are not clear at present, a marked increase in the production of different cytokines including tumour necrosis factor and the activation of nuclear factor-kB have been observed in the CP heart (24,39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed varying degrees of depression in gene expression for SL, SR and MF proteins, as well as defects in subcellular organelles during the development of heart failure in patients and experimental animal models (1)(2)(3)(4)(5)(6). Accordingly, it has been suggested that cardiac dysfunction in failing hearts is due to subcellular remodelling as a consequence of changes in cardiac gene expression (2,(7)(8)(9).…”
mentioning
confidence: 99%